PERAN PENGAWASAN, MOTIVASI, DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN ( Studi kasus pada UKM Fremilt di Surakarta ) - EVI NURHIDAYAH (JURNAL WIDYA GANECWARA, 2020)
This study aims to determine the effect ofssupervision, motivation and work discipline on employee achievement. at Freemilt UKM in Surakarta. The population in this study at Surakarta Fremilt UKM was 67 employees. The data used in this study are primary data. This type of research is quantitative. The technique of multiple linear regression data analysis. F-test results prove that the factors of supervision, motivation and work discipline simultaneously affect employee performance. in Freemilt UKM in Surakarta, Central Java, where the value of Fcount = 85.395> Ftable = 2.70 with a significance of 0.000 <0.05. T test results prove thats upervision has a positive and significant effect on employee performance in Freemilt SMEs in Surakarta with a tcount = 2.478> ttable = 1.997 and a significance of 0.016 <0.05. Motivation has a positive and significant effect on employee achievement in Freemil UKM in Surakarta with a tcount of 4.350> ttable = 1.997 with a significance of 0.000 <0.05. Work discipline has a positive and significant effect on employee performance in Freemilt SMEs in Surakarta with a tcount of 1.814 <ttable = 1.997 with a significance of 0.074> 0.05.